The mediating role of resilience between perceived social support and sense of security in medical staff following the COVID-19 pandemic: A cross-sectional study - He, Qingxia; Xu, Peng; Wang, Huajun; Wang, Shibin; Yang, Lulu; Ba, Zhiqiong; Huang, Huigen (Frontiers in Psychiatry, 2023)
Background The COVID-19 pandemic not only posed a serious threat to public life and health but also had a serious impact on people's mental health, especially that of medical staff. Perceived social support is an important factor in one's sense of security. Objective Following the COVID-19 pandemic, the goal is to explore the potential mediating role of resilience in the relationship between perceived social support and the sense of security of Chinese medical personnel. Methods The multi-stage proportionally stratified convenience sampling method was adopted to select 4,076 medical professionals from 29 hospitals in Guangdong Province between September 2020 and October 2020. The Sense of Security Scale for Medical Staff, the Chinese version of the Connor-Davidson Resilience Scale, and the Perceived Social Support Scale were employed in this study. For statistical analysis and structural equation modeling (SEM), the SPSS 23.0 and Amos 24.0 software packages were used. Regression analysis was used to select the control variables to be included in the SEM. SEM analysis was conducted to verify the mediating effect of resilience on the relationship between perceived social support and a sense of security. Results Pearson's correlation analysis showed that perceived social support and resilience were positively associated with a sense of security (correlation coefficients range from 0.350 to 0.607, P < 0.01), and perceived social support (correlation coefficients range from 0.398 to 0.589, P < 0.01) was positively associated with resilience. Structural equation modeling revealed that resilience played a partial mediating role in the association between perceived social support and a sense of security (60.3% of the effect of perceived social support on security was direct, and 39.7% of the effect was mediated by resilience). Conclusions Hospital managers should make efforts to develop resilience. Interventions based on resilience should be developed to enhance the perception of social support and strengthen one's sense of security.